Внесок родини Дудіків-Харченко у наукову роботу та створення колекцій рослин Національного ботанічного саду ім. М.М. Гришка НАН України - Chuvikina, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
Contribution of two generations of the Dudyk-Kharchenko family – selectionists, flower-growers (F.S. Dudyk, K.D. Kharchenko and N.M. Dudyk) – in creation of plant collections and scientific advances of M.M. Gryshko National Botanical Gardens was shown. The vital way of these family scientists is lighted up.